Inhibition of (pro)renin Receptor Contributes to Renoprotective Effects of Angiotensin II Type 1 Receptor Blockade in Diabetic Nephropathy - Zhang, Lin; An, Xiao-Fei; Ruan, Xin; Huang, Dong-Dong; Zhou, Li; Xue, Hong; Lu, Li-Min; He, Ming (Frontiers in Physiology, 2017)
Aims: Renal renin-angiotensin system (RAS) plays a pivotal role in the development of diabetic nephropathy (DN). Angiotensin II (Ang II) type 1 receptor (AT1R) blockade elevates (pro)renin, which may bind to (pro)renin receptor (PRR) and exert receptor-mediated, angiotensin-independent profibrotic effects. We therefore investigated whether PRR activation leads to the limited anti-fibrotic effects of AT1R blockade on DN, and whether PRR inhibition might ameliorate progression of DN. Methods: To address the issue, the expression of RAS components was tested in different stages of streptozotocin (STZ)-induced diabetic rats (6, 12 and 24 weeks) and 6-week AT1R blockade (losartan) treated diabetic rats. Using the blocker for PRR, the handle region peptide (HRP) of prorenin, the effects of PRR on high glucose or Ang II-induced proliferative and profibrotic actions were evaluated by measurement of cell proliferation, matrix metalloproteinase-2 (MMP-2) activity, activation of extracellular signal-regulated kinase 1/2 (ERK1/2) and transforming growth factor-β1 (TGF-β1) expression in rat mesangial cells (MCs). Results: PRR was downregulated in the kidneys of different stages of diabetic rats (6, 12 and 24 weeks). Moreover, 6-week losartan treatment further suppressed PRR expression via upregulating AT2R, and ameliorated diabetic renal injury. HRP inhibited high glucose and Ang II-induced proliferative and profibrotic effects in MCs through suppressing TGF-β1 expression and activating MMP-2. Meanwhile, HRP enhanced losartan’s anti-fibrotic effects through further inhibiting phosphorylation of ERK1/2 and TGF-β1 expression. Moreover, the inhibitive effect of HRP on Ang II-induced TGF-β1 expression depended on the regulation of PRR expression by AT2R. Conclusions: Our findings suggest that PRR inhibition contributes to renoprotection against diabetic nephropathy by AT1R blockade.